The immature stages of Tropisternus (Pleurhomus) sahlbergi (Sharp) (Coleoptera: Hydrophilidae), with considerations on the primary chaetotaxy of Tropisternus Soliera - Torres, Patricia L. M.; Michat, Mariano C.; Archangelsky, Miguel (Zootaxa, 2011)
The preimaginal stages of Tropisternus (Pleurhomus) sahlbergi (Sharp, 1883) are described for the first time, including illustrations and photographs of the egg case, all larval instars and pupa. The descriptions emphasize on the morphometry and chaetotaxy, following current standards in larval descriptions within Hydrophilidae. Preliminary evidence is presented for a placement of Pleurhomus Sharp, 1833 within Tropisternus Solier, 1834, in agreement with a recent phylogenetic analysis based on adult characters. Tropisternus (P.) sahlbergi is characterized by a brown to dark brown head capsule without color pattern, mandibles with strongly serrated inner margins, a short seta PA11 in comparison to PA14, the absence of seta AN8, the absence of a distal secondary seta on the outer margin of the first maxillary palpomere and the dorsal surface of the mentum almost entirely covered by spinulae.